Design strategy of a Cu-based catalyst for optimizing the performance in the electrochemical CO2 reduction reaction to multicarbon alcohols. Issue 44 (28th October 2022) - Ni, Zhiyuan; Wang, Peng; Quan, Fan; Guo, Rui; Liu, Chunming; Liu, Xuanwen; Mu, Wenning; Lei, Xuefei; Li, Qingjun
Abstract : The electrochemical CO2 reduction reaction (ECRR) is a promising method to reduce excessive CO2 emissions and achieve a sustainable carbon cycle. Abstract : The electrochemical CO2 reduction reaction (ECRR) is a promising method to reduce excessive CO2 emissions and achieve a sustainable carbon cycle. Due to the high reaction kinetics and efficiency, copper-based catalysts have shown great application potential for preparing multicarbon (C2+ ) products. C2+ alcohols have high economic value and use-value, playing an essential role in modern industry. Therefore, we summarize the latest research progress of the ECRR to synthesize C2+ alcohols on Cu-based catalysts and discuss the state-of-the-art catalyst design strategies to improve CO2 reduction performance. Moreover, we analyzed in detail the specific reaction pathways for the conversion of CO2 to C2+ alcohols based on DFT calculations. Finally, we propose the problems and possible solutions for synthesizing C2+ alcohols with copper-based catalysts. We hope that this review can provide ideas for devising ECRR catalysts for C2+ alcohols.